Perancangan Game Edukasi Kulnas (Kuliner Nusantara) dalam Melestarikan Kekayaan Nusantara menggunakan Visual Basic - Ono, Rosalia Sonia; Ismiati, Maria Bellaniar (MEANS (Media Informasi Analisa dan Sistem), 2019)
Traditional food or culinary archipelago is an ethnic or country identity. In Indonesia traditional food can be found easily in every province. However, many Indonesian people do not know their traditional food and prefer western food or western food. They also have no knowledge of the ingredients used to make western food. One of the causes of this phenomenon is because nowadays Indonesian people tend to play cooking games from abroad or games that do not add to their insight. It cannot be denied that the number of games is quite a lot, on the other hand the number of local games to introduce traditional or culinary food of the Indonesian archipelago is very low and even rarely found. Therefore, this study made an educational game to introduce various traditional foods from all regions in Indonesia and what ingredients were used in making these foods. This game was developed using Visual Basic with the beginning of storyboarding (design) from the archipelago culinary education game, then the design and coding process of the national game. The game itself can be played on personal computers, by possessing various menus such as introducing 3 foods that are typical of 32 provinces which of course are rarely heard and what ingredients are used in making these foods. And quiz knowledge about the materials used to make typical foods in each province.